Tip-enhanced electric field : a new mechanism promoting mass transfer in oxygen evolution reactions - Liu, Peng (2021)
The slow kinetics of oxygen evolution reaction (OER) causes high power consumption for electrochemical water splitting. Various strategies have been attempted to accelerate the OER rate, but there are few studies on regulating the transport of reactants especially under large current densities when the mass transfer factor dominates the evolution reactions. Herein, Nix Fe1- x alloy nanocones arrays (with ≈2 nm surface NiO/NiFe(OH)2 layer) are adopted to boost the transport of reactants. Finite element analysis suggests that the high-curvature tips can enhance the local electric field, which induces an order of magnitude higher concentration of hydroxide ions (OH- ) at the active sites and promotes intrinsic OER activity by 67% at 1.5 V. Experimental results show that a fabricated NiFe nanocone array electrode, with optimized alloy composition, has a small overpotential of 190 mV at 10 mA cm-2 and 255 mV at 500 mA cm-2 . When calibrated by electrochemical surface area, the nanocones electrode outperforms the state-of-the-art OER electrocatalysts. The positive effect of the tip-enhanced local electric field in promoting mass transfer is also confirmed by comparing samples with different tip curvature radii. It is suggested that this local field enhanced OER kinetics is a generic effect to other OER catalysts.